Hak Perempuan dan Kesetaraan Gender dalam Perspektif Filsafat Hukum - Bangun, Budi Hermawan (Universitas Negeri Semarang, 2020)
This paper focuses on the origin and development of women’s rights and the principle of gender equality in the perspective of legal philosophy.Women's rights as part of Human Rights were born and developed from thoughts about the importance of protecting and fulfilling the rights of women who belong to vulnerable groups and also to ensure gender equality.Although it has been accommodated in various national and international legal instruments, de facto fulfillment of women's rights must still be ensured by each country.Fulfillment of women's rights in the perspective of legal philosophy seeks to obtain justice as the highest goal of the law itself and ensure the realization of the principle of equality before the law.